2018
DOI: 10.2298/jmmb160718012z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two iron bullets from the royal ammunition factory of Eugi (Spain)

Abstract: In this work, a comparative analysis of two iron bullets found in The Royal Ammunition Factory of Eugi in Navarra (Spain) was performed. Both bullets presented a spherical shape with a relatively good state of preservation, belonging to the last years of the factory production (1766-1850). Several techniques such as microhardness, X-ray fluorescence (XRF), light (LM) and scanning electron microscopy (SEM), optical mission spectroscopy (OES) and energy dispersive X-ray spectroscopy (EDX) analysis were used in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
0
0
1
Order By: Relevance
“…Grey cast iron (ternary iron-carbon-silicon alloys) is characterised by the content of more than 2 wt% C as graphite particles, the increased carbon content reducing the melting temperature of the alloy [28,31,32]. Cast iron objects are often cast in a sand mould containing a cavity of the desired shape, consisting of cope and drag (top and bottom parts) with an upper pouring space (cup and sprue), as well as a vent and riser [33] (p. 102, Figure 6).…”
Section: Cast Ironmentioning
confidence: 99%
See 1 more Smart Citation
“…Grey cast iron (ternary iron-carbon-silicon alloys) is characterised by the content of more than 2 wt% C as graphite particles, the increased carbon content reducing the melting temperature of the alloy [28,31,32]. Cast iron objects are often cast in a sand mould containing a cavity of the desired shape, consisting of cope and drag (top and bottom parts) with an upper pouring space (cup and sprue), as well as a vent and riser [33] (p. 102, Figure 6).…”
Section: Cast Ironmentioning
confidence: 99%
“…The high concentration of manganese in cast objects (>0.5 wt% Mn) results in high-quality products with only a small amount of porosity defects attributable to the sand casting. The presence of manganese in cast iron products, to prevent the formation of gas holes and porosity, indicates a post-1839 manufacturing date [31][32][33].…”
Section: Cast Ironmentioning
confidence: 99%
“…The differences in the graphite morphology are attributed to the different cooling rate of the samples, there is a lower solidification rate for the samples of 25.4 mm than the samples of 12.7 mm in thickness. The center of the plates of 25.4 mm remains hotter than the ones of 12.7 mm or the external surface, therefore, a major graphite formation is induced for the thicker sample [22], the super-cooling degree of the molten iron was small and graphite had excellent nucleation ability to form type-A graphite. Lacaze et al [11] reported that a type-A graphite distribution forms at low solidification rates and as the rate increases, a transition of type-D graphite distribution will occur.…”
Section: Optical Microscopymentioning
confidence: 99%
“…Las técnicas de microscopía óptica, microscopía electrónica de barrido (SEM, por sus siglas en inglés) y análisis elemental por energía dispersiva de rayos X (EDX por sus siglas en inglés), han sido ampliamente utilizadas en el análisis de muestras arqueológicas, logrando información sobre la microestructura, procesos de manufactura, grietas y abolladuras que sugieren posibles usos o sucesos y la composición elemental de una serie de objetos como artefactos metálicos (Leal, 2010), cerámicas (Amaya et al, 2008), fibras (Arenas et al, 2015), obras pictóricas (Barrantes-Madrigal et al, 2021), por mencionar algunos ejemplos. En el caso del análisis de municiones arqueológicas, se han realizado numerosos estudios dentro de los cuales se mencionan por ejemplo, Zalakain et al (2017). Los autores realizaron un estudio comparativo entre dos municiones encontradas en la Real Fábrica de Municiones de Eugi en Navarra utilizando las técnicas de caracterización SEM y EDX, que les permitió conocer los procesos de manufactura.…”
Section: Introductionunclassified